2014
DOI: 10.1080/02699931.2014.981250
|View full text |Cite
|
Sign up to set email alerts
|

The bright side of brooding: State orientation increases positive emotions about positive outcomes

Abstract: Research has by and large shown the negative effects of state orientation, that brooding over past events (i.e., state orientation) leads to more negative emotions and less well-being than quickly getting over past events (i.e., action orientation). However, this past research has primarily focused on how people cope with negative events and bad outcomes. The present research focuses on how people cope with positive events with good outcomes. Study 1 found that state-oriented people felt better after a windfal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…Further, considering the AOF scale categorizes the participants as zero or one, it is not necessary to compare averages as it would be with a scale containing items on a Likert scale. This reasoning is in line with the existing literature in the field that does not include the AOF scale in factor analysis (e.g., Allemand et al, 2008;Dholakia, Tam, Yoon, & Wong, 2016;Van Putten, 2015).…”
Section: Constructssupporting
confidence: 86%
See 1 more Smart Citation
“…Further, considering the AOF scale categorizes the participants as zero or one, it is not necessary to compare averages as it would be with a scale containing items on a Likert scale. This reasoning is in line with the existing literature in the field that does not include the AOF scale in factor analysis (e.g., Allemand et al, 2008;Dholakia, Tam, Yoon, & Wong, 2016;Van Putten, 2015).…”
Section: Constructssupporting
confidence: 86%
“…The authors found that higher social relatedness increased the selfregulation ability of state oriented students in a negative mood. Van Putten, 2015 Laboratory design involving three studies and 259 students.…”
Section: Study Empirical Setting Key Findingsmentioning
confidence: 99%
“…Prior research has shown that adverse effects of state orientation are mitigated when positive close relationships are made salient (Koole et al, 2005 ; Puterman et al, 2010 ; Koole and Fockenberg, 2011 ; Chatterjee et al, 2013 , 2017 ). Indeed, when conditions are sufficiently supportive, state-oriented people may even outperform action-oriented people (Koole et al, 2005 ) and experience more positive emotions (Van Putten, 2015 ). Thus, state-oriented people are not necessarily destined to poor life outcomes as long as adequate support is available.…”
Section: Discussionmentioning
confidence: 99%
“…Extant literature across several domains has established that the personality trait of action orientation versus state orientation influences behaviour. These domains include social psychology (e.g., Allemand et al, 2008;Van Putten, 2015) educational psychology (e.g., Bossong, 1994;Brunstein, 1994), consumer research (e.g., Bagozzi, Baumgartner, & Yi, 1992), decision making (e.g., Stiensmeier-Pelster, 1994;Van Putten et al, 2010), sport science (e.g., Strang, 1994), and work place performance (Diefendorff et al, 2000). An overview of these studies is provided in Table 3.…”
Section: Measuring Self-regulation: Action Orientation and State Orientationmentioning
confidence: 99%
“…It is expected that negotiators who are state-oriented will struggle to make a considered decision in a demanding international negotiation. PSI theory argues that state-oriented individuals are influenced by emotion and past failure, as they struggle to both self-regulate and use their extension memory to make decisions (Van Putten, 2015;Van Putten et al, 2010). So, even when they have high power and the opportunity to ignore the anger and not make a concession, it is likely they will be influenced by the demanding context and concede more than an actionoriented negotiator.…”
Section: The Joint Influence Of Bargaining Power and Self-regulation Abilitymentioning
confidence: 99%